2022
DOI: 10.1590/1980-5373-mr-2022-0239
|View full text |Cite
|
Sign up to set email alerts
|

Analyze the Effect of Crater Cutting Tool Wear Modeling in the Machining of Aluminium Composite

Abstract: The present investigation is used to analyze the effect of crater wear modeling in the machining of aluminium composite. Response surface methodology (RSM) is one of the best optimization technique used to bring out the optimal values of speed, feed and depth of cut for attain minimum surface roughness, cutting tool temperature and tool wear. AA7075 alloy with 15wt% of silicon carbide has been investigated in the dry machining condition. The double layered TiCN/Al 2 O 3 coated tool was preferred. The worn surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…The optimization was performed using RSM, MLR, ANN, and DFA. The author in [97] used the RSM approach to observe the surface peak of Al7075/SiC. The prediction models were constructed in turn using Taguchi and RSM and concluded that the creation of wear is caused by abrasion between the aluminum, silicon, magnesium, copper, and silicon carbide reinforcing particles [98].…”
Section: Aluminium Reinforced With Silicon (Al/si)mentioning
confidence: 99%
“…The optimization was performed using RSM, MLR, ANN, and DFA. The author in [97] used the RSM approach to observe the surface peak of Al7075/SiC. The prediction models were constructed in turn using Taguchi and RSM and concluded that the creation of wear is caused by abrasion between the aluminum, silicon, magnesium, copper, and silicon carbide reinforcing particles [98].…”
Section: Aluminium Reinforced With Silicon (Al/si)mentioning
confidence: 99%